THU0048 Radius 1: Correlation between serious infection events (SIES) and rheumatoid arthritis (RA) disease activity in patients requiring a change in therapy. (23rd January 2014) - Weaver, A.; Troum, O.; Hooper, M.; Koenig, A.; Chaudhari, S.; Feng, J.-Y.; Wenkert, D.
Abstract : Background: The RA Disease-Modifying Anti-Rheumatic Drug (DMARD) Intervention and Utilization Study–1 (RADIUS 1) was a real-world, prospective, 5-year, observational study of 4968 patients (aged ≥18 y) with RA (per 1987 American Rheumatism Association criteria) who had required a new biologic or nonbiologic DMARD (addition or switch). Although DMARDS and comorbidities may increase risk of SIE, RA disease activity itself may also increase infectious risk. Objectives: To evaluate the impact of RA disease activity, measured by the Clinical Disease Activity Index (CDAI), on the risk of developing ≥1 SIE in RADIUS 1 patients (pts). Methods: Data from RADIUS 1 pts who received ≥1 dose of DMARDs and had been followed up for >1 day were analyzed. SIEs occurring while on DMARD treatment were analyzed, excluding SIEs without a recorded date (n=11) or recorded DMARD; multiple SIEs occurring on the same day were analyzed as 1 event. Comorbidities at baseline were classified into 2 mutually exclusive groups—(1) RA-associated extra-articular manifestations (eg, Felty syndrome, pulmonary nodules) and (2) comorbidities that were not extra-articular manifestations of RA (eg, renal disease)—as well as into nonexclusive groups: asthma and COPD, ischemic heart disease, prior hospitalization for infection and cancers. Disease activity was defined as remission (CDAI ≤2.8), low (CDAI 2.8–10.0), moderate (CDAI 10–22) or high (CDAI >22). The Anderson-Gill model was used to calculate hazard ratios (HRs) and associated 95% CIs. Results: Analysis included 4084 pts: 81% white, 76% female, 22% with extra-articular manifestations thought to be RA associated, and 5% with comorbidities not attributable to RA. Prednisone was used by 56% of pts, with 24% of these pts receiving >10 mg/d. At baseline, mean disease duration was 7.3 years and mean CDAI was 35.7 (3% in CDAI remission; 15% low, 30% moderate, 49% high disease activity). 347 SIEs were observed, and 271 pts experienced ≥1 SIE; 33 pts had 2 SIEs, 7 had 3 SIEs, 7 had 4 SIEs, and 1 had 9 SIEs. HRs, unadjusted and adjusted (for age, sex, rheumatoid factor positive, disease duration, late onset [age >65 y], health assessment questionnaire, extra-articular RA manifestations, concomitant RA medications, and medical and medicinal factors contributing to increased risk of SIE), showed that a 5-unit increase in CDAI was associated with an 11.9% (unadjusted) and 7.9% (adjusted) increased risk of SIE (95% CIs, 1.09–1.15 and 1.04–1.12, respectively). Unadjusted/adjusted HRs (95% CI) for low (3.09/2.58 [1.34–7.12/1.12–5.96]) moderate (5.81/4.04 [2.56–13.2/1.77–9.23]), and high (7.50/4.55 [3.31–16.99/1.99–10.39]) disease activity indicated that more severe RA disease activity, measured by CDAI, was associated with increased risk of SIE. Conclusions: With and without controlling for covariates, increased RA disease activity significantly raised the risk of SIEs. This study was sponsored by Immunex, a wholly owned subsidiary of Amgen Inc. and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: A. Weaver Consultant for: Amgen Inc, Speakers Bureau: Amgen Inc, O. Troum Grant/Research support from: Amgen Inc, Consultant for: Amgen Inc, M. Hooper Employee of: Amgen Inc, A. Koenig Employee of: Pfizer Inc, S. Chaudhari Consultant for: Amgen Inc, J.-Y. Feng Employee of: Amgen Inc, D. Wenkert Employee of: Amgen Inc